2019
DOI: 10.1186/s13287-019-1420-9
|View full text |Cite
|
Sign up to set email alerts
|

Does co-transplantation of mesenchymal and spermatogonial stem cells improve reproductive efficiency and safety in mice?

Abstract: BackgroundSpermatogonial stem cell transplantation (SSCT) is a promising therapy in restoring the fertility of childhood cancer survivors. However, the low efficiency of SSCT is a significant concern. SSCT could be improved by co-transplanting transforming growth factor beta 1 (TGFβ1)-induced mesenchymal stem cells (MSCs). In this study, we investigated the reproductive efficiency and safety of co-transplanting spermatogonial stem cells (SSCs) and TGFβ1-induced MSCs.MethodsA mouse model for long-term infertili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 54 publications
(57 reference statements)
0
12
0
Order By: Relevance
“…MSC transplantation improved the expression of germ cell markers in the testes and can be proposed as a suitable method for the treatment of infertility. Several possible mechanisms of testicular function restoration during MSC-induced tissue regeneration have been shown: (1) MSCs may be involved in the suppression of antisperm antibodies (ASA) [ 147 ]; (2) MSCs can reduce factors that lead to infertility through reduction of apoptosis [ 127 ]; (3) MSCs can reduce oxidative stress [ 139 ]; (4) MSCs can stimulate testosterone production [ 126 ] with differentiation into Laydig cells [ 148 ]; (5) MSCs can differentiate into target cells [ 133 ]; (6) the transplanted cells secrete growth factors such as bone morphogenetic proteins (BMPs) and transforming growth factor beta (TGF-β), which are male germ cell inducing factors with ability to stimulate restoration of the recipient’s cellular function [ 149 ]; (7) MSCs connect with endogenous cells, restoring the function of damaged cells [ 150 ]; (8) MSCs reverse the glycolysis and glycogenesis imbalance in sperm by regulating Akt/glycogen synthase kinase 3 (GSK3) axis [ 151 ]; and (9) MSCs can alter expression of some spermatogenesis-related miRNAs and their target genes [ 134 ].…”
Section: Msc Therapy In Animal Model Of Azoospermiamentioning
confidence: 99%
“…MSC transplantation improved the expression of germ cell markers in the testes and can be proposed as a suitable method for the treatment of infertility. Several possible mechanisms of testicular function restoration during MSC-induced tissue regeneration have been shown: (1) MSCs may be involved in the suppression of antisperm antibodies (ASA) [ 147 ]; (2) MSCs can reduce factors that lead to infertility through reduction of apoptosis [ 127 ]; (3) MSCs can reduce oxidative stress [ 139 ]; (4) MSCs can stimulate testosterone production [ 126 ] with differentiation into Laydig cells [ 148 ]; (5) MSCs can differentiate into target cells [ 133 ]; (6) the transplanted cells secrete growth factors such as bone morphogenetic proteins (BMPs) and transforming growth factor beta (TGF-β), which are male germ cell inducing factors with ability to stimulate restoration of the recipient’s cellular function [ 149 ]; (7) MSCs connect with endogenous cells, restoring the function of damaged cells [ 150 ]; (8) MSCs reverse the glycolysis and glycogenesis imbalance in sperm by regulating Akt/glycogen synthase kinase 3 (GSK3) axis [ 151 ]; and (9) MSCs can alter expression of some spermatogenesis-related miRNAs and their target genes [ 134 ].…”
Section: Msc Therapy In Animal Model Of Azoospermiamentioning
confidence: 99%
“…On the other hand, the presence of mesenchymal cells in PTCs may also benefit future transplantation purposes as it has been postulated that mesenchymal cells can contribute to the colonization potential of (cultured) human spermatogonial cell fractions. This idea is substantiated by a recent report of Kadam et al [ 66 ], who showed increased efficiency of spermatogonial colonization after co-transplanting mouse SSCs with mouse bone-marrow derived MSCs in a allogeneic transplantation model.…”
Section: Discussionmentioning
confidence: 71%
“…A possible solution was reported in animal studies, where co-transplanting SSCs and TGFβ1-treated mesenchymal stem cells resulted in reproductive efficacy that is as good as using SSCs alone. The authors demonstrated similar reproductive capacity after transplantation of just half the number of SSCs (Kadam, Ntemou, Onofre, Van Saen, & Goossens, 2019). The second promising method is the freezing of testicular tissue for later autotransplantation.…”
Section: Challeng E S and Future Per S Pec Tive Smentioning
confidence: 91%